The Charge of the Ultracapacitors. - Schindall, J.
Nanotechnology takes energy storage beyond batteries. A bank of ultracapacitors releases a burst of energy to help a crane heave its load aloft; they then capture energy released during the descent to recharge. Buses, trams, and garbage trucks powered by the devices all run for short stretches before stopping, and it's during braking that the ultracapacitors can partially recharge themselves from the energy that's normally wasted, giving the vehicles much of the juice they need to get to their next destinations.
Keywords: Energy storage; Supercapacitors; Ultracapacitors